Debt reduction: the basis and shape of a new strategy - Jeffrey Sachs; Josef Kneer (Intereconomics, 1990)
The burden of past restructuring of the external debt of developing countries has been distributed asymmetrically among creditors owing to the lack of incentives for voluntary debt reduction. “New creditors” have been deterred from lending voluntarily because their claims would inevitably be added to a mountain of bad debt. Therefore new ways of reducing debt and debt servicing must be found. Our authors suggest a process of concerted debt reduction designed to ensure that all the creditor banks involved play an equal part.
Keywords: 330; Indebtedness